Conceptual Analysis of Brand Love in Online Brand Community - Khamwon, Anon; Pornsrimate, Kanyawee (KKBS Journal of Business Administration and Accountancy, 2018)
Online brand community is commonly viewed solely as a tool for engaging with customers online.It has unavoidably given rise to build a strong online brand community and brand love representing highly meaningful customer relationship management instruments for firms. For this reason, this study proposes a conceptual model to further understand the effect of sense of online community andbrand community identification on brand love leading to brand evangelism and branding co-creation. By documenting these issues is critical due to the fact that the advantage of online brand community is crucial tool to enhance the feeling of love towards brand, favourable customer behaviours and also a successful long-term relationship with customers.